Effects of a ready-to-drink thermogenic beverage on resting energy expenditure, hemodynamic function, and subjective outcomes - Christian Rodriguez; Matthew T. Stratton; Patrick S. Harty; Madelin R. Siedler; Jake R. Boykin; Jacob J. Green; Dale S. Keith; Sarah J. White; Brielle DeHaven; Alexandra Brojanac; Ethan Tinoco; Lem W. Taylor; et al. (Taylor & Francis Group, 2023)
Background Thermogenic supplements are often consumed by individuals seeking to improve energy levels and reduce body fat. These supplements are sold in powdered or ready-to-drink (RTD) forms and consist of a blend of ingredients such as caffeine, green tea extract, and other botanical compounds. While there is evidence that thermogenic supplements can positively affect resting energy expenditure (REE), the effect varies based on the combination of active ingredients. Additionally, there is some concern that thermogenic supplements may cause unwanted side effects on hemodynamic variables, like heart rate (HR) and blood pressure (BP). Therefore, further investigation into the efficacy and safety of commercially available products is warranted. Methods Twenty-eight individuals (14 F, 14 M; age: 23.3 ± 3.9 yrs; height: 169.4 ± 8.6 cm; body mass: 73.3 ± 13.1 kg) completed two visits in a randomized, double-blind, crossover fashion. Each visit began with baseline REE, HR, and BP assessments, which were followed by ingestion of an active RTD thermogenic beverage (RTD; OxyShred Ultra Energy) or placebo (PL). Assessments were repeated at the intervals of 35-50- and 85-100-minutes post-ingestion. In addition, subjective outcomes of energy, focus, concentration, alertness, and mood were collected five times throughout each visit. Repeated-measures analysis of variance was performed with condition and time specified as within-subjects factors and sex and resistance training (RT) status as between-subjects factors. Statistical significance was accepted at p < 0.05. Results A significant condition × time interaction was observed for REE (p < 0.001). Higher REE values were demonstrated at 35-50 min (0.08 ± 0.02 kcal/min; p = 0.001; 5.2% difference) and 85-100 min (0.08 ± 0.02 kcal/min; p = 0.001; 5.5% difference) after RTD ingestion as compared to PL. No significant condition × time interactions were observed for respiratory quotient, HR, or BP. Condition main effects indicated lower HR (3.0 ± 0.9 bpm; p = 0.003), higher SBP (3.5 ± 1.1 mm Hg; p = 0.003) and higher DBP (3.5 ± 0.9 mm Hg; p < 0.001) in RTD as compared to PL, irrespective of time. Condition × time interactions were observed for all subjective outcomes (p ≤ 0.02). Post hoc tests indicated statistically significant benefits of the RTD over PL for energy, focus, concentration, and alertness, without significant differences for mood after correction for multiple comparisons. Sex and RT status were not involved in interactions for any outcomes, except for a Sex × RT status interaction for energy, indicating higher energy ratings in non-resistance-trained vs. resistance-trained males. Conclusions These data suggest that acute ingestion of a thermogenic RTD beverage significantly increases REE, and this elevated caloric expenditure is sustained for at least 100 minutes following ingestion. Furthermore, the RTD beverage increased measures of energy, focus, concentration, and alertness as compared to placebo. While minor differences in hemodynamic variables were observed between conditions, all values stayed within normal ranges. Individuals aiming to increase energy expenditure may benefit from acute ingestion of an RTD thermogenic supplement.